2011
DOI: 10.1097/shk.0b013e31822f36b0
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of a Phosphatidylcholine-Enriched Diet in Lipopolysaccharide-Induced Experimental Neuroinflammation in the Rat

Abstract: Our goal was to characterize the neuroprotective properties of orally administered phosphatidylcholine (PC) in a rodent model of systemic inflammation. Sprague-Dawley rats were killed at 3 h, 1 day, 3 days, or 7 days after i.p. administration of lipopolysaccharide (LPS) to determine the plasma levels of tumor necrosis factor α (TNF-α) and interleukin 6 cytokines. The control group and one group of LPS-treated animals were nourished with standard laboratory chow, whereas another LPS-treated group received a spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…Regardless of its possible abundance in the membranes, liver concentrations of endogenous GPC are significantly depleted after hemorrhagic shock, a prototype of systemic IR injury [7], and previous data suggested us that exogenous GPC may influence the tissue reactions in IR scenarios [12, 13, 31]. Herein, we have outlined a novel route of action for the molecule.…”
Section: Discussionmentioning
confidence: 93%
“…Regardless of its possible abundance in the membranes, liver concentrations of endogenous GPC are significantly depleted after hemorrhagic shock, a prototype of systemic IR injury [7], and previous data suggested us that exogenous GPC may influence the tissue reactions in IR scenarios [12, 13, 31]. Herein, we have outlined a novel route of action for the molecule.…”
Section: Discussionmentioning
confidence: 93%
“…Extensive researches up to date suggest that phosphatidylcholine plays a pivotal role in many important areas including maintaining memory and nerve signaling, as a precursor to important neurotransmitters and attenuating acute renal failure and liver dysfunction [17-19]. A number of recent studies have demonstrated an anti-inflammatory potential for PC and its metabolites in various conditions linked to leukocyte activation, including ischemia [20], oxidative stress [21] and endotoxin-induced injuries [22,23]. PUFA, one component of PC, also has been shown to modulate the inflammatory reactions [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Inducible NO synthaseYderived NO has been implicated in several aspects of the inflammatory cascade in experimental or clinical colitis. We earlier reported that PC treatment inhibited the expression and activity of iNOS isoenzyme in vivo (5, 6) and decreased GI tissue NO x levels in endotoxemic rats (9), and in the present study, PC supplementation significantly decreased the stable end product of NO in the colon tissue in both phases of colitis.…”
Section: Discussionmentioning
confidence: 55%
“…The activity of MPO as a marker of tissue leukocyte infiltration was measured on the pellet of the homogenate (9). Briefly, the pellet was resuspended in K 3 PO 4 buffer (0.05 M; pH 6.0) containing 0.5% hexa-1,6-bisdecyltriethylammonium bromide.…”
Section: Tissue Mpo Activitymentioning
confidence: 99%
See 1 more Smart Citation